Three-arm robot-assisted thoracoscopic surgery for locally advanced N2 non-small cell lung cancer - Cheng, Xinghua; Li, Chongwu; Huang, Jia; Lu, Peiji; Luo, Qingquan (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
Video-assisted thoracoscopic surgery (VATS) is now recognized as the standard treatment of early staged lung cancer due to improved postoperative recovery and equivalent oncological efficacy as compared to the conventional open approach (1,2). However, its use in locally advanced lung cancer has not been adopted by the majority of thoracic surgeons. Technical challenges and the concern on insufficient lymph node dissection are the main obstacles to the application of VATS in this group of patients (3).